Early Postoperative Inflammatory Responses Following Primary Total Hip Arthroplasty Using Different Antibiotic-Loaded Bone Cement Formulations: A Prospective Observational Cohort Study - Nicolas Catalin Ionut Ion; Sorin Radu Fleaca; Bogdan Axente Bocea; Cosmin Ioan Mohor; Mihai-Dan Roman; Călin-Ilie Mohor; Alexandru Florin Diconi; Alexandru Turcu; Iustin-Ilie Tutuianu; Mihai Faur; Vanesa-Maria Veres; Vicențiu-Vasile Vereș; et al. (Journal of Clinical Medicine, 2026)
Introduction: Periprosthetic joint infection (PJI) remains one of the most challenging complications following total hip arthroplasty (THA). Antibiotic-loaded bone cement (ALBC) provides high local antibiotic concentrations and is widely used in patients at increased risk of infection. Although several dual-antibiotic formulations have been investigated, their influence on the early postoperative inflammatory response has not been directly compared. Methods: In this prospective observational cohort study, 35 patients undergoing primary cemented THA between January 2025 and January 2026 were allocated to one of five ALBC regimens according to routine clinical practice: gentamicin alone, gentamicin–vancomycin, gentamicin–clindamycin, gentamicin–meropenem, or gentamicin–tobramycin (n = 7 per group). Serum C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and leukocyte count were measured preoperatively and on postoperative Days 1, 3, and 7. Longitudinal analyses accounting for within-patient correlations were performed to assess the effects of treatment group, postoperative time, and the group × time interaction. Day-specific between-group comparisons using one-way analysis of variance (ANOVA), with eta-squared (η2) as an effect-size measure, were performed as secondary analyses, with Bonferroni adjustment applied to post-hoc pairwise comparisons. Results: All treatment groups demonstrated progressive reductions in postoperative inflammatory markers. Longitudinal analysis demonstrated significant effects of treatment group, postoperative time, and the group × time interaction for CRP and ESR (all p < 0.001). For leukocyte count, significant effects of time and the group × time interaction were observed (both p < 0.001), whereas the overall group effect was not statistically significant (p = 0.071). Secondary day-specific analyses showed significant between-group differences in CRP, with comparatively lower values observed in the gentamicin–meropenem group. Several pairwise differences in CRP and ESR remained statistically significant after Bonferroni adjustment, whereas no pairwise differences in leukocyte counts remained significant after correction. Conclusions: Different antibiotic-loaded PMMA formulations were associated with distinct early postoperative inflammatory profiles. Gentamicin–meropenem was associated with comparatively lower CRP and ESR values; however, these exploratory findings do not establish superior infection-preventive efficacy and require confirmation in larger studies.